Association between integrase strand transfer inhibitor use with insulin resistance and incident diabetes mellitus in persons living with HIV: a systematic review and meta-analysis. Issue 1 (8th February 2023) - Mulindwa, Frank; Kamal, Habiba; Castelnuovo, Barbara; Byonanebye, Dathan M; Schwarz, Jean-Marc; Bollinger, Robert; Brusselaers, Nele
Abstract : Whether integrase strand transfer inhibitors (INSTIs) are associated with a higher risk of incident type 2 diabetes mellitus (DM) than other antiretroviral therapies (ART) needs to be established. MEDLINE, Embase, Web of Science, and ClinicalTrials.gov registries were searched for studies published between 1 January 2000 and 15 June 2022. Eligible studies reported incident DM or mean changes in insulin resistance measured by Homeostatic Model for Insulin Resistance (HOMA-IR) in patients on INSTIs compared with other ARTs. We performed random-effects meta-analyses to obtain pooled relative risks (RRs) with 95% CIs. A total of 16 studies were pooled: 13 studies meta-analyzed for incident diabetes with a patient population of 72 404 and 3 for changes in HOMA-IR. INSTI therapy was associated with a lower risk of incident diabetes in 13 studies (RR 0.80, 95% CI 0.67 to 0.96, I 2 =29%), of which 8 randomized controlled trials demonstrated a 22% reduced risk (RR 0.88, 95% CI 0.81 to 0.96, I 2 =0%). INSTIs had a lower risk compared with non-nucleoside reverse transcriptase inhibitors (RR 0.75, 95% CI 0.63 to 0.89, I 2 =0%) but similar to protease inhibitor-based therapy (RR 0.78, 95% CI 0.61 to 1.01, I 2 =27%). The risk was lower in studies with longer follow-up (RR 0.70, 95% CI 0.53 to 0.94, I 2 =24%) and among ART-naïve patients (RR 0.78, 95% CI 0.65 to 0.94, I 2 =3%) but increased in African populations (RR 2.99, 95% CI 2.53 to 3.54, I 2 =0%). In conclusion, exposure to INSTIs was not associated with increased risk of DM, except in the African population. Stratified analyses suggested reduced risk among ART-naïve patients and studies with longer follow-up. International Prospective Register of Systematic Reviews (PROSPERO) registration number: CRD42021273040.